Boundary element analysis of elastic fields in non-horizontally layered halfspace whose horizontal boundary subject to tractions. (October 2018) - Xiao, S.; Yue, Z.Q.; Xiao, H.T.
Abstract: This paper presents a boundary element analysis of linear elastic fields in a layered halfspace whose material interface planes are not parallel to its horizontal boundary surface. This boundary element analysis uses the generalized Kelvin solution in a multilayered elastic solid (or the so-called Yue's solution) for taking into account the non-horizontally layered structures. It also adopts the infinite boundary elements for evaluating the influence of a far-field region. It further adopts both the discontinuous finite and infinite boundary elements to discretize the boundary surface around the strike lines of the inclined material interfaces. It uses Kutt's numerical quadrature to evaluate the strongly singular integral in the discretized boundary integral equation. Numerical examples are presented to illustrate the effects of the non-horizontally layered materials to the displacements and stresses induced by the tractions on the horizontal boundary surface. Two non-horizontally layered halfspace models are used for numerical analysis and illustrations. Numerical results show that across the material interface, the elastic displacements are non-smoothly continuous to different degrees and some stress components can have very high values at and around the interface planes, which can be important to tensile or shear failure in non-homogeneous materials.